Research on Measurement Error Distribution and Optimization Measurement Method of Clamp-On Ultrasonic Flowmeter in Downstream Pipeline Disturbance - Zhongzhi Yang; Wei Wang; Xianjie Liu; Xin Chen; Xia Li; Xiaofeng Lu (Sensors)
Clamp-on ultrasonic flowmeters serve as an important tool for on-site testing of gas flow meters. However, its accuracy is significantly affected by the actual flow field, thus limiting its application scenarios. To address this issue, this study focuses on typical industrial disturbance structures and obtains the evolution and distribution of non-ideal flow fields downstream of disturbances through experiments and numerical simulations, as well as their effects on velocity and flow measurement errors. The results indicate that when traditional reflection or diagonal measurements were used in the downstream of disturbances, the flow deviation was largely dependent on the installation position and angle of the clamp-on ultrasonic flowmeter. This introduced significant uncertainty and bias, rendering it impossible to correct measurement results through quantitative coefficients. Utilizing a dual-channel measurement method can enhance measurement accuracy. When two sets of sensors perpendicular to each other were used to combine the reflection measurement path, the deviation fluctuation downstream of disturbances can be effectively controlled within the range of ±2%, irrespective of the installation angle. This measurement approach significantly reduced the distance limitations on the distance of the straight pipe section during the use of clamp-on ultrasonic flowmeters.